Impact of knowledge sharing on the evolution and growth of family businesses in Wenzhou, P.R. China. - Su, You Yi. (2010)
Asian country have historically been the hotbeds for the establishment and growth of family businesses. This was more evident in urban and semi urban settings where all members of immediate and extended family were recruited to run service-oriented or production-oriented businesses. Business system relying on family and other personal ties for security are common throughout most of East and Southeast Asia (Perkins, 2000). Tan & Fock, (2001) stated that more than 50% businesses are family controlled in East Asia.